Seeing the Stove as World: Significance (Bedeutung) in the Early Wittgenstein1. (14th August 2018) - Balaska, Maria
Abstract: What is it to see a stove as world (als Welt) and why does the early Wittgenstein use such a curious example to describe what it means to see something as significant (bedeutend)? I argue that Wittgenstein's odd choice can be best understood in the light of a conceptual relation between value and semantic meaning. To that purpose, I draw attention to his use of the word Bedeutung to denote value, and to the direct connection he draws between seeing as world and seeing with the whole logical space. To see a stove as bedeutend, I conclude, is to see it against the background of the propositional contexts in which a stove figures meaningfully.